(untitled) (Publicaciones en Ciencias y Tecnología, 2022)
Sometimes the functionality of the software leaves outside the ease of use, which is the feature known today as Usability. Knowing its conceptual evolution and evaluation parameters between 1985 and 2020, is the objective of this article that reports the results obtained from the bibliographic review carried out in a search in Google Scholar, Microsoft Academic, World Wide Science and websites that were identified as referents and support. In the findings, the concept of usability was originally identified as the degree of ease of use, and then it was a contribution to the quality of the software to evaluate the security, accessibility, and support for the user experience today. The appearance of disaggregated usability parameters was also found, with eight being the most frequently repeated, and only one persists over time: Do not load the working memory to the user, thus seeking the satisfaction of the use of the software, it is also identified three parameters of ISO 9241-11: 2018 that are: efficiency, effectiveness, and satisfaction, the most recognized today.